The Role of Social Institutions in Improving the Welfare of the Elderly in Ambon - Hobarth Williams Soselisa (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
This study aims to identify, manage, and analyze data to understand the role of social institutions in improving the welfare of the elderly in Ambon City. It is hoped that the results of this study can reduce the research gap that has been mentioned and contribute to social institutions in efforts to improve social welfare.Bottom of Form Social institutions play a crucial role in providing various services and assistance for the elderly, such as social assistance, material assistance, and empowerment programs that focus on meeting the physical, psychological, and social needs of the elderly. This study uses a qualitative approach with a case study method, where data is obtained through in-depth interviews, observations, and documentation of a number of social institutions operating in Ambon City. The research findings show that social institutions have a significant contribution to improving the welfare of the elderly through the provision of health services, social assistance, and economic empowerment programs that can increase the independence of the elderly. However, there are obstacles faced by social institutions, such as limited funds and manpower, which have an impact on the quality of services provided. This study suggests the importance of optimizing the role of social institutions by increasing support from the government and the community to improve the welfare of the elderly in Ambon City. Keywords: The role of social institutions, Elderly Welfare,